17-20 year-old female basketball players' competitive adaptation upon promotion to higher-class team - Chernov, S. V.; Andryushchenko, L. B.; Averyasova, J. O.; Andryushchenko, O. N. (Theory and Practice of Physical Culture, 2017)
The study was designed to develop a set of practical tools to facilitate competitive adaptation (CA) of junior highly-skilled female basketball players upon their promotion to a higher-class team. We generally consider the process of the junior highly-skilled female basketball players adaptation upon promotion to a higher-class team as the active efficiency-building process to secure their transition from the habitual low-active and low-efficient performance to the highly-active and highly-efficient performance in the top-intensity game environment at a reasonably fast pace rather than via a long-term habituation. The article overviews findings of a few study reports on the issues of sport reserve training for the Russian national women's basketball team that gave the grounds to offer a set of practical tools for the team coaches to facilitate the adaptation strategies duly individualized for every player to secure the team being highly fit for competitions, plus to improve the quality of the players` selection process for the backup (reserve) teams. The study data and analyses demonstrated that the junior highly-skilled female basketball players` adaptation to the higher-class teamwork may be much more efficient if the coaches pay a special attention to a number of social and psychological impact-factors including the team attitudes to a new team member, changes in statuses assessable by the relevant social metrics, and the relevant promotional and self-rating aspects.